Philosophical foundations of human rights - Cruft, Rowan; Liao, S. Matthew; Renzo, Massimo (Philosophical foundations of law., 2015)
What makes something a human right? What is the relationship between the moral foundations of human rights and human rights law? What are the difficulties of appealing to human rights? This book offers the first comprehensive survey of current thinking on the philosophical foundations of human rights. Divided into four parts, this book focusses firstly on the moral grounds of human rights, for example in our dignity, agency, interests or needs. 'Secondly, it looks at the implications that different moral perspectives on human rights bear for human rights law and politics. Thirdly, it discusses specific and topical human rights including freedom of expression and religion, security, health and more controversial rights such as a human right to subsistence. The final part discusses nuanced critical and reformative views on human rights from feminist, Kantian and relativist perspectives among others. The essays represent new and canonical research by leading scholars in the field. Each part is comprised of a set of essays and replies, offering a comprehensive analysis of different positions within the debate in question.The introduction from the editors will guide researchers and students navigating the diversity of views on the philosophical foundations of human rights. -- cover